Kinerja Marshall Immersion pada Campuran Asphalt Concrete Binder Course (Ac-Bc) dengan Penambahan Limbah Buttom Ash Sebagai Subtitusi Agregat Halus - Lesmana, Arief; Abrar, Aidil; Abdillah, Nuryasin (Sekolah Tinggi Teknologi Dumai, 2024)
Asphalt is one of the materials used for road construction. To reduce the amount of need for asphalt, namely by minimizing the use of asphalt base materials, or by increasing the quality of asphalt in the mixture by adding additional ingredients in the mixture that can overcome the weaknesses of asphalt. Waste management, The use of solid fuels in the form of coal as an energy source produces bottom ash and fly ash waste, which can cause environmental pollution. This study aims to examine the effect of using bottom ash as a substitute for fine aggregate on stability, melting (flow), voids in the mixture (VIM), voids in mineral aggregate (VMA), voids filled with asphalt (VFA) and Marshall quotient of asphalt concrete mixtures. This research was conducted in the laboratory of the Dumai High School of Technology, using asphalt content of 6%, 8% and 10% with each grade representing 4 samples of test objects. From the research it was found that the use of bottom ash waste as a substitute for fine aggregate in asphalt mixtures affected the Flow, VIM, and VFA values which were not included in the specifications determined by the 2010 Revision 3 binamarga. The use of bottom ash waste as a substitute for fine aggregate in the AC-BC asphalt mixture cannot be used because the high VIM value makes the asphalt bleed and the low VFA value causes the asphalt mixture to become hollow or porous so that the asphalt mixture is not airtight and easily destroyed.